Living identities in the mosaic of consumption resistance practices - Alcântara, Valderí de Castro; Cavazza, Bruna Habib; Campos, Alyce Cardoso; Prado, José Willer do; Rezende, Daniel Carvalho de (Revista de Negócios, 2019)
In this article, we aimed to understand how discourses and other social consumption resistance practices are articulated in the processes of identity reconstruction. The corpus was formed by in-depth interviews with consumption resistance practitioners. The analyses followed the directions of the Social Theory of Discourse, from the notions of social practices and discourse meanings. Our contribution is that the consumption resistance practitioners articulate discourses and other social practices in the processes of identity reconstruction marked by re-significances and contradictions, being therefore a hybrid and tensional field that forms a mosaic of consumption resistance practices. Specifically, we discovered that conflicting discourse orders influenced consumption resistance practices in a interdiscursive way, which articulated the reconstruction of identities. This included scientific, political, religious, animal ethics, environmental, social, and conscious consumption discourses.